Probabilistic Load Flow Solution Considering Optimal Allocation of SVC in Radial Distribution System - Ahmed, Walaa; Selim, Ali; Kamel, Salah; Yu, Juan; Jurado, Francisco (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
This paper proposes a solution procedure for probabilistic load flow problem considering the optimal allocation of Static Var Compensator (SVC) in radial distribution systems. Pareto Envelope-based Selection Algorithm II (PESA-II) with fuzzy logic decision maker is developed to determine the optimal location and size of SVC based on the minimum total power losses and Voltage Deviation (VD). Combined cumulants and gram-chalier expansion are used for solving the probabilistic load flow problem. The proposed algorithm is tested on 33-bus and 69-bus distribution systems. The developed algorithm gives an acceptable solution with low number of iterations and less computation cost compared with the Monte Carlo method.
Keywords: particle swarm optimization; radial distribution system; probabilistic load flow; SVC; IJIMAI